Influence of annual training cycle on threshold power and reaction of blood antioxidative stress indices during a standard rowing test - Basta, P.; Skarpanska-Stejnborn, A.; Pilaczynska-Szczesniak, L. (Human Movement, 2008)
The study presents a comparative analysis of the threshold power and exercise-induced changes in the blood antioxidative stress parameters in a standard rowing test between two measurements (terms of the study). Basic procedures. The study comprised 15 subjects aged between 20 and 23 years, members of the Polish National Youth Rowing Team at the end of preparatory phase of the annual training cycle in 2003 (Term I) and in 2004(Term II). At both terms selected indices of antioxidative stress and the threshold power (AT4) induced by physical exercise with graded intensity were analyzed. Main findings. At the second term of the study, as compared with the first term, a higher activity of superoxide dismutase in blood samples at rest was found. At the same time a decreased activity of glutathione peroxidase in blood samples after exercise was observed. The level of lipid peroxidation products in red cells (TBARS) regarded as the marker of free radical-induced damage was also significantly lower. The results indicated that at the second term of the study the rate of anaerobic metabolism measured with the blood lactate level was lower than at the first term despite the fact that the threshold power values between both terms of the study did not reveal any significant differences. Conclusions. The annual training cycle in young rowers, although not contributing significantly to the increase of the threshold power, induced positive changes in their antioxidant defense systems; namely, the lower level of TBARS after exercise and the higher SOD activity at rest.